Efek Musik pada Tingkat Kecemasan Atlet Sebelum Pertandingan - Marisa Noviyanti (JSKK (Jurnal Sains Keolahragaan dan Kesehatan), 2022)
Anxiety experienced by athletes before a match often interferes with the performance of athletes on the field, music is often used as a tool to relax and minimize anxiety before a match. However, there has been no further research examining the impact of music on athletes' anxiety before competition. Therefore this research was conducted to contribute to the scope of sports achievements, especially basketball. The method used in this research is descriptive quantitative, using the anxiety questionnaire approach given to athletes before the competition. The total participants in this study were 87 athletes who took part in basketball competitions. All samples were divided into two groups, each group was required to listen to music 30 minutes before the match and the other group did not listen to music. The results showed that there was a significant difference between the music and control groups in reducing the athlete's anxiety level before the competition. This study shows that there is an impact of real music on reducing athletes' anxiety before the competition. It is hoped that in the future there will be further research that compares types of music, so that there is a more conical reference which type of music is more effective in reducing athlete's anxiety before competition.